Geographical Study of the Location of the Traditional Beverage Industry (Moke) Based on Weber's Theory in Kokowahor Village, Kangae District, Sikka Regency - Evodius Meyendro Ama Nair; Muhammad Husain Hasan; Arfita Rahmawati (Tinta Emas Institute, 2025)
The traditional Moke beverage industry in Kokowahor Village, Kangae District, Sikka Regency, is part of the local culture and a source of community income. This study aims to analyze the location of the Moke industry based on Alfred Weber's industrial location theory, focusing on transportation and labor cost efficiency. The method used is a quantitative approach with data collection techniques through interviews, observation, documentation, and field studies. Data were analyzed using a locational triangle approach to determine the optimal location of the industry. The results show that most Moke industries are located close to raw material sources and markets, thus reducing transportation costs. In addition, the workforce used comes from families or the surrounding community, so labor costs are relatively low. These findings are in line with Weber's principle that industrial location is determined by cost minimization. This research is expected to serve as a reference in the development of local industries sustainably and strengthen the study of economic geography through the application of location theory in the context of traditional industries.